From structures to properties: The impacts of two modification methods on pectin/sodium carboxymethyl cellulose composite film for advanced packaging materials - Hua Chen; Xiaonan Bian; Haoyuan Wang; Kaijie Shang; Zhiheng Zhao; Yijun Liu; Xue Lin; Xuewu Guo; Xiaoping Hu; Lu Wang (Food Chemistry: X)
The effect of two modification methods, ultrasound and tannic acid (TA), on the structural, physicochemical, antioxidant, and antibacterial attributes of pectin‑sodium carboxymethyl cellulose (CMC) based composite film were assessed. The chemical structure and morphological analyses of the composite films revealed a 10 min ultrasound or adding 8 % TA improved the intermolecular interaction forces of the polymer, substantially leading to the formation of more dense gel network structures. Furthermore, the application of a 10 min ultrasound or the integration of 8 % TA caused a significant increase in the composite film's water resistance and mechanical strength. The incorporation of 10 % TA into the composite film induced the highest antioxidant activities and optimal antibacterial efficacies against both Staphylococcus aureus and Escherichia coli. Overall, the addition of appropriate TA has demonstrated a more pronounced enhancement of the physicochemical, antioxidant, and antibacterial properties of the composite film when compared to the modification through ultrasound.